Comparison of Nurses’ Image in Korean Online Newspaper Articles before and after COVID-19: A Text Mining Analysis (Medico Legal Update, 2021)
Background/Objectives: This study investigated nurse-related keywords which were presented togetherwith nurse on phrase, clauses or sentence of documents or conversations in the Korea online newspaperarticles.Methods/Statistical analysis: Text mining, which is a common method of analysis for large datasets, wasused to analyze the changes in nurses’ image before and after COVID-19. A total of the linking wordswith nurse were calculated by the number of presentation on online newspaper article in Naver before andafter COVID-19. In order to identify the meaning of the words, clustering of the collected linking wordsby categories was analysed and the characteristics of each cluster were classified. Over 5,000 articles wereidentified as targets for a keyword analysis.Findings: The most frequently presenting words were hospital, medical and patient. Before COVID-19, thewords related to ‘workplace bullying’ were highly presented and after COVID-19, the words related to ‘care’were highly presented.Improvements/Applications: With analyzing the trends of changes and characteristics of words byCOVID-19 and clusters, we attempted to investigate the image of nurse that the public think and feel aboutnurse.